Effects of isoinertial training on muscle power, endurance, isometric strength, and balance: randomized clinical trial in patients with post-ACL reconstruction - Ramesh Chandra Patra; Som Gupta; A. Yashudas; Sanjeev Mahajan (Trials)
Abstract Background ACL reconstruction surgery leads to temporary limitations in knee movement due to weakness in the quadriceps, swelling, and stiffness. Effective therapy is necessary to regain strength and functionality. While flywheel resistance training enhances strength and eccentric loading, there is limited knowledge about its effectiveness in conjunction with conventional rehabilitation methods. This study evaluates the impact of both conventional rehabilitation and isoinertial therapy on muscle power, endurance, isometric strength, and balance in patients following ACL repair. Methods A total of 96 out of 136 patients aged 18 to 45 who had been randomly assigned to groups were included 3 weeks post-procedure. Over 6 weeks, 47 patients in group A (n = 47) participated in both isoinertial training and conventional therapy protocals while in group B (n = 49) followed a conventional rehabilitation protocol for just 30 min daily. To assess the patients’ muscle power, endurance, isometric strength, and balance, a flywheel ergometer (D11 Plus; Desmotec, Biella, Italy) was utilized both before and after the 6-week treatment period. Results Group A had statistically significant increases in eccentric muscular power (p = 0.0001), whereas there was no noticeable difference between the two groups in isometric strength, balance, or concentric power (p = 0.731, p = 0.786, and p = 0.815, respectively). Conclusion The finding indicates that isometric strength, balance, and both concentric and eccentric muscular power were successfully improved by both 6-week interventions: traditional rehabilitation alone and in conjunction with isoinertial training. But when compared to traditional therapy alone, the isoinertial training group showed better gains in muscular endurance. There were no discernible variations in the groups’ isometric strength or balance results. The study also emphasizes how isoinertial training can effectively increase eccentric power. Trial registration. The ethics approval number is LPU/IEC/2018/01/09. Registered in the Clinical Trials Registry of India under CTRI/2019/06/019858 dated 23/09/2021.